Saponins and Polyphenolics of Methanol Leaf Extract of Boswellia dalzielii Hutch - , Divine A. Onobrudu (Archives of Current Research International, 2017)
The aim of this study was to investigate saponins and polyphenolic constituents of methanol leaf extract of Boswellia dalzielii Hutch.The qualitative phytochemistry was based on using reagents known to produce a particular color change which is distinct to that compound, while gas chromatography flame ionization detector (GC-FID) was used for the quantitative phytochemistry. The result revealed 24 polyphenolic compounds with protocatechuic acid (32.08%), catechin (23.77%), quercetin (8.35%), luteolin (20.15%) and kaempferol (12.79%) as the predominant constituents, and 11 phytocompounds of saponin with sapogenin (89.98%) and saponine (0.09%) being the predominant constituents. The experimental results indicate that the methanolic extract of Boswellia dalzielii Hutch leaves could be a potent antioxidant agent.